Sistem Pendukung Keputusan Penerimaan Karyawan Menggunakan Metode Analytical Hierarchy Process (AHP) Studi Kasus : RB. Nilam Sari Tembilahan - Bayu Rianto (RJOCS (Riau Journal of Computer Science), 2016)
This study developed a decision support system (DSS) with memamfaatkan method of analytical hierarchy process (AHP) as the admission process in the selection of employees. Inthis selection process used several criteria to determine which applicants will be accepted. DSS helps corporate leaders in memtuskan which applicants will be selected. This thesis researchfocuses on how to design and implement programs and is intended to facilitate the calculation.AHP is used as a method in the calculation of the employee's admission selection.